Questions about sensitive perception in Thomas Aquinas: sensible awareness and intentional similitude - Landim Filho, Raul (Discurso, 2023)
My aim in this article is to analyze and to articulate the main notions of external sense perception according to Thomas Aquinas: reception of form without matter, intentional reception of the natural form, sensible awareness and intentional sensible similitude. As I will show, these notions connected to the function of Common Sense, are the foundations of Thomist realism.